Penerapan Metode Rula untuk Mengidentifikasi Resiko Kecelekaan pada Divisi Gudang di PT. Dalwa Anugrah Hasaniyah - Alfaris, M Salman; Riyana, Iis; Mustaqim, Mustaqim (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT. Dalwa Anugrah Hasaniyah's water production still relies on human power to carry out its production activities. At PT. Dalwa Anugrah Hasaniyah has a section for producing mineral water which is processed manually in a bending and standing position. Activities in the process of washing bottles into the machine are (1) inserting labels into bottles, (2) lifting bottles containing water into cartons, and (3) moving cartons containing mineral water to pallets. The activities carried out by workers have a high risk and cause complaints of pain. To overcome this problem, it is necessary to carry out work posture analysis to assess and evaluate worker posture. Based on the results of the Nordic Body Map questionnaire, workers experienced complaints in the waist, arms and back. The results of the RULA assessment show that the activity has a score of 7, meaning that the activity has a high risk of musculoskeletal disorders so that further investigation and changes need to be corrected as soon as possible.